2022
DOI: 10.1039/d2se00455k
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on performance modulation and mechanism study of silicon-based anodes

Abstract: Silicon-based anode composites are being pursued extensively as anode materials because of their high specific capacities, reduced voltage platforms, and abundant natural resources. However, this type of anodes suffers from...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 142 publications
(160 reference statements)
0
4
0
Order By: Relevance
“…30 In recent years, many researchers have adopted the attempt of combining Si with metal to reduce the volume change and improve the electrical conductivity. 31 For example, various structures of Si/Cu nanocomposites have been reported. Zhou et al 32 successfully prepared Cu 3 Si@Si core-shell nanoparticles using the solid phase reaction.…”
Section: Introductionmentioning
confidence: 99%
“…30 In recent years, many researchers have adopted the attempt of combining Si with metal to reduce the volume change and improve the electrical conductivity. 31 For example, various structures of Si/Cu nanocomposites have been reported. Zhou et al 32 successfully prepared Cu 3 Si@Si core-shell nanoparticles using the solid phase reaction.…”
Section: Introductionmentioning
confidence: 99%
“…15 It has been shown that a higher oxygen content of SiO x corresponds to a lower capacity and better cyclability. 19 The initial theorical capacity of the SiO x anode is 2615 mAh/g, and its volume expansion during lithiation/delithiation is ∼160% 18 (typically between 100 and 300% 11 ). One major limitation of the formation of Li silicates and oxides during the first cycle is the low initial coulombic efficiency (ICE), which must be addressed when relying on SiO x -based anodes.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical capacity of the Si anode is approximately 4200 mAh/g, which is more than 10 times that of the graphite anode. However, because Si undergoes an alloying process, its volume expansion rate (up to 400% 11 ) is considerably higher than that of graphite, resulting in limited cyclability. In addition, Li ions are continuously consumed during the lithiation/delithiation process because of the repeated formation of the solid electrolyte interface (SEI) layer, which leads to low coulombic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of portable electronic products, electric vehicles, and energy storage systems, anode materials with high specific capacities, such as Si, SiO, and lithium metal, attract more attention in Li-ion batteries (LIBs). [1][2][3] Due to their higher specific capacity (>1600 mA h g −1 ) than graphite (372 mA h g −1 ) and a smaller volume change (200%) than Si, SiO-based anode materials are regarded as promising highcapacity candidates. However, some intrinsic problems seriously limit their widespread utility for LIBs.…”
Section: Introductionmentioning
confidence: 99%